Assessment of Urban Land Use Pattern of Birgunj City: A Geographical Approach - Dube, Shiva Kant (Academic Voices: A Multidisciplinary Journal, 2019)
Birgunj has experienced rapid growth due to migration from peripheral districts and villages for security and other reasons. Most of the fertile agricultural fields are rapidly converting into residential and commercial areas. The changes in land use from 1998 to 2005 and further to 2016 were computed using toposheet maps and satellite images adopting qual-quant method. It has been observed that about 598 hectare of agricultural land converted to built-up area from 1998 to 2005 with the annual increment rate of 20.9 percent. However, the increment rate decreased to 8.1 percent during 2005 to 2016 resulting the conversion of 897 hectare agriculture land into built-up area. In terms of change in percent, the built up area increased by 146 percent from 1998 to 2005. It is interesting to note that despite the gap of 11 years between 2005 and 2016, the percent of increment has slowed down to 89 percent only in later period. On the other hand, the agricultural area decreased by 9 percent and 14 percent between 1998 and 2005 and 2005 and 2016 respectively. Thus, there is urgent need to implement effective policy by concerned authorities to reduce the negative consequences of haphazard urbanization.